Competition for a hotel in Irkutsk - Grigoryeva, Elena (project baikal, 2023)
The competition for a hotel in Solnechny microdistrict is considered in the context of the competitions held in Irkutsk since the mid-2010s. Spatial and organisational features of the competition and the teams are characterised. The participation of Irkutsk architects in the competition is highlighted.
Keywords: competitions; hotel; teams of architects; Irkutsk; Head Water